Antioxidant properties of naturally brown-colored cotton fibers. Issue 3 (February 2016) - Ma, Mingbo; Luo, Shaohong; Hu, Zhihua; Tang, Zhirong; Zhou, Wenlong
Naturally brown-colored cotton (NBCC) fibers have been reported as having excellent antibacterial properties. In this study, the antioxidant properties of NBCC fibers were investigated . The results demonstrate that the antioxidant capacity of NBCC is significantly higher than that of white cotton. An NBCC variety with a darker color has a much higher capacity in which the 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) and 2, 2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) free radical scavenging activities are 6.9 and 6.1 times those of white cotton, respectively. The antioxidant properties of NBCC were durable after scouring and laundering. The phenolic pigment composition in the fibers was found to contribute to their antioxidant properties. The results presented have furthered the understanding of the polyfunctional properties of NBCC fibers and their pigment components.